Analisis Kepemimpinan, Disiplin Kerja, Pengawasan Dan Pengaruhnya Terhadap Kinerja Aparatur Sipil Negara Pada Badan Kepegawaian Kota Mojokerto - Rohmatiah, Ahadiati; Anggraini, Novellita Sicillia (Universitas Merdeka Madiun, 2019)
The purpose of this study were (1) To test / analyze the influence in partial leadership, work discipline and supervision of the State Civil Apparatus performance Mojokerto; (2) To examine / analyze the influence of variables simultaneously leadership, work discipline and supervision of the State Civil Apparatus performance Mojokerto; and (3) To examine / analyze the dominant influence on the performance of the State Civil Administrative Personnel Board Mojokerto.Respondents in this study is the State Civil Apparatus (ASN) Employment Board Mojokerto totaling 89 people. Data collection techniques in this study using questionnaires and documentation. While the data analysis technique using multiple linear regression analysis.The findings showed that (1) partially no effect Significant variables of leadership, work discipline and supervision of the Administrative Performance at the State Civil Personnel Board Mojokerto; (2) simultaneously was no significant effect of leadership variable, work discipline and supervision of the Civil Administrative Performance at the State Personnel Board Mojokerto and (3) Variable leadership dominant influence on the performance in the State Civil Administrative Personnel Board Mojokerto.